Genetic deletion of galectin-3 enhances neuroinflammation, affects microglial activation and contributes to sub-chronic injury in experimental neonatal focal stroke - Chip, Sophorn (Brain Behav Immun, 2016)
The pathophysiology of neonatal stroke and adult stroke are distinct in many aspects, including the inflammatory response. We previously showed endogenously protective functions of microglial cells in acute neonatal stroke. We asked if galectin-3 (Gal3), a pleotropic molecule that mediates interactions between microglia/macrophages and the extracellular matrix (ECM), plays a role in early injury after transient middle cerebral occlusion (tMCAO) in postnatal day 9–10 mice. Compared to wild type (WT) pups, in Gal3 knockout pups injury was worse and cytokine/chemokine production altered, including further increase of MIP1α and MIP1β levels and reduced IL6 levels 72 h after tMCAO. Lack of Gal3 did not affect morphological transformation or proliferation of microglia but markedly attenuated accumulation of CD11b(+)/CD45(med-high) cells after injury, as determined by multi-color flow cytometry. tMCAO increased expression of αV and β(3) integrin subunits in CD11b(+)/CD45(low) microglial cells and cells of non-monocyte lineage (CD11b(−)/CD45(−)), but not in CD11b(+)/CD45(med-high) cells within injured regions of WT mice or Gal3−/− mice. αV upregulated in areas occupied and not occupied by CD68(+) cells, most prominently in the ECM, lining blood vessels, with expanded αV coverage in Gal3−/− mice. Cumulatively, these data show that lack of Gal3 worsens subchronic injury after neonatal focal stroke, likely by altering the neuroinflammatory milieu, including an imbalance between pro- and anti-inflammatory molecules, effects on microglial activation, and deregulation of the composition of the ECM.